Pseudomonas aeruginosa quorum sensing molecules correlate with clinical status in cystic fibrosis - Barr, Helen L.; Halliday, Nigel; Cámara, Miguel; Barrett, David A.; Williams, Paul; Forrester, Doug L.; Simms, Rebecca; Smyth, Alan R.; Honeybourne, David; Whitehouse, Joanna L.; Nash, Edward F.; Dewar, Jane; et al. (European Respiratory Society, 2015)
ABSTRACT Pseudomonas aeruginosa produces quorum sensing signal molecules that are potential biomarkers for infection. A prospective study of 60 cystic fibrosis patients with chronic P. aeruginosa, who required intravenous antibiotics for pulmonary exacerbations, was undertaken. Clinical measurements and biological samples were obtained at the start and end of the treatment period. Additional data were available for 29 of these patients when they were clinically stable. Cross-sectionally, quorum sensing signal molecules were detectable in the sputum, plasma and urine of 86%, 75% and 83% patients, respectively. They were positively correlated between the three biofluids. Positive correlations were observed for most quorum sensing signal molecules in sputum, plasma and urine, with quantitative measures of pulmonary P. aeruginosa load at the start of a pulmonary exacerbation. Plasma concentrations of 2-nonyl-4-hydroxy-quinoline (NHQ) were significantly higher at the start of a pulmonary exacerbation compared to clinical stability ( p<0.01). Following the administration of systemic antibiotics, plasma 2-heptyl-4-hydroxyquinoline ( p=0.02) and NHQ concentrations (p<0.01) decreased significantly. In conclusion, quorum sensing signal molecules are detectable in cystic fibrosis patients with pulmonary P. aeruginosa infection and are positively correlated with quantitative measures of P. aeruginosa. NHQ correlates with clinical status and has potential as a novel biomarker for P. aeruginosa infection.